Intimate partner violence amongst undergraduate nursing students - Kordom, A (South African Journal of Higher Education, 2016)
Intimate partner violence is reported to be rife among the student population at tertiary institutions and the general population. Yet the abuse is under diagnosed by nurses in health care settings. Research indicates that nurses’ personal experiences of this type of abuse play a role in the management of survivors. Hence, the study investigated the prevalence and factors associated with intimate partner violence among the undergraduate nursing student population at a tertiary institution in the Western Cape, South Africa. A self-administered questionnaire was completed by the stratified random sample. The reported life time prevalence of intimate partner violence included psychological, physical, financial abuse and sexual abuse. Intimate partner violence was significantly associated with the educational status of the respondent’s mother, financial support and witnessing of abuse during childhood. A support structure is needed to prepare the undergraduate student nurses emotionally before commencing with their training in the management of survivors of IPV.